HIV-1 prevalence, drug resistance, and associated factors in the urban Ethiopian population - Teshiwal Deress; Abebaw Worede; Abebe Birhanu; Mekonnen Girma (Scientific Reports)
Abstract Despite progress in HIV control, gaps persist in understanding the prevalence, drug resistance, and associated factors in urban Ethiopia. This cross-sectional study analyzed data from 19,136 consenting participants (aged 15–64 years) for interview and blood testing in the 2017–2018 Population-based HIV Impact Assessment (PHIA) survey to assess HIV-1 prevalence, drug resistance mutations, and associated factors. Participants confirmed to be living with HIV (PLHIV) provided additional samples for CD4 + T-cell counts, viral load testing, and drug resistance analysis. Forty-three samples were analyzed for viral subtyping and drug resistance profiling, of which 42 samples successfully amplified. Data were analyzed using descriptive statistics and logistic regression. The overall HIV-1 prevalence was 3%. Among genotyped samples, 79.1% harbored drug resistance mutations, with high rates of resistance to Non-Nucleoside Reverse Transcriptase Inhibitors (NNRTIs) (78.8%) and Nucleoside Reverse Transcriptase Inhibitors (NRTIs) (66.7%). Regarding associated factors, females had 1.7 times higher odds of HIV infection than males (AOR = 1.7). Participants aged 35–44 and 45–54 had significantly higher odds of infection (AOR = 6.7 for both) compared to those aged 15–24. Lower educational attainment (primary school: AOR = 2.5; secondary school: AOR = 2.2) was associated with increased HIV prevalence compared to post-secondary education. Previously married individuals had higher infection odds than never-married participants (AOR = 2.7). Geographically, residents of Gambella showed significantly higher odds (AOR = 2.8) compared to those in Tigray. This study identified a high HIV-1 prevalence in Ethiopia, along with elevated virological failure rates, a significant proportion of PLHIV unaware of their status, and widespread drug resistance. Sex, age, education level, marital status, and region were the identified factors associated with HIV-1 prevalence. To improve treatment outcomes and curb transmission, Ethiopia should strengthen HIV prevention strategies focused on vulnerable populations, enhance testing and linkage to care, and implement routine drug resistance monitoring.